2012
DOI: 10.1136/bmj.e1756
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cost effectiveness of mobile phone supported self monitoring of asthma: multicentre randomised controlled trial

Abstract: Objective To determine whether mobile phone based monitoring improves asthma control compared with standard paper based monitoring strategies.Design Multicentre randomised controlled trial with cost effectiveness analysis.Setting UK primary care.Participants 288 adolescents and adults with poorly controlled asthma (asthma control questionnaire (ACQ) score ≥1.5) from 32 practices.Intervention Participants were centrally randomised to twice daily recording and mobile phone based transmission of symptoms, drug us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
200
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(209 citation statements)
references
References 41 publications
1
200
1
2
Order By: Relevance
“…Telemonitoring solutions for chronic conditions management are being assessed currently through multiple clinical [3][10] and economic studies [6] [7]. Some of the preliminary results conclude that the use of these technologies is not related to an improvement in health indicators [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Telemonitoring solutions for chronic conditions management are being assessed currently through multiple clinical [3][10] and economic studies [6] [7]. Some of the preliminary results conclude that the use of these technologies is not related to an improvement in health indicators [20].…”
Section: Discussionmentioning
confidence: 99%
“…While the literature is progressively focusing on the cost-effectiveness of applying new technologies to diabetes management [6] [7], the focus should be on promoting patient education and consciousness to deal with the disease. In the case of non-communicable diseases, where long duration and slow progression require concrete actions on patient lifestyle, the Information and Communication Technologies (ICT) may contribute to provide the individual and supporting careers with solutions to manage therapies, increase awareness and promote healthy selfmanagement habits [7] [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al (2011) found that the use of a smartphone app in the self-management of asthma led to significant improvements in clinical outcomes and a reduction in the number of visits to the hospital emergency department. However, Ryan et al (2012) suggested that the similar smartphone app for asthma patients had no statistically significant effect on clinical outcomes or the frequency of hospital admissions. A systematic review by NICE (2017) found that the use of a 'Smartinhaler' in treating asthma only improved clinical outcomes in two of five randomised controlled trial (RCT) studies, although greater adherence to treatment was observed in all cases.…”
Section: Evidence On Impact From Related Interventionsmentioning
confidence: 99%
“…1 In a world where digital technology has revolutionized the way we work, shop and manage our finances, it is unsurprising that digital systems are suggested as potential solutions. 2,3 However, recent evidence suggesting that telehealth may not be quite the panacea that was promised [4][5][6] has led to discussions on the mechanisms and role of digital technology in respiratory care. This series of papers, reflects the debate and we hope that, by offering reasoned arguments, it may help to shape a new paradigm.…”
mentioning
confidence: 99%